India : new security challenges and vulnerabilities - Rudra, Kalyan (Delhi, 2003)
This book is to sensitize security personnel in various State and Central security organizations about the various sinister facets of the current scenario and to emphasize the importance of reorientation and training of the forces and the need for upgradation of their weaponry and wherewithal, apart from the most important requirement of improvement in the process of intelligence generation
Keywords: National security -India